Optimization of 2.4 GHz CMOS Low Noise Amplifier Using Hybrid Particle Swarm Optimization with Lévy Flight - Joshi D.; Dash S.; Malhotra A.; Sai P.V.; Das R.; Sharma D.; Trivedi G. (My University, 2025)
In this paper, a metaheuristic based on the hybrid of particle swarm optimization technique and simulated annealing scheme with Levy flight (l-HPSO) is proposed. The optimization technique incorporates Levy flight principle to improve convergence. Particle swarm optimization (PSO) is applied to construct initial solutions for simulated annealing (SA) scheme and these initial solutions are used to decompose the entire search space into different annealing regions. Further, each annealing region is exploited to search for optimum solution using simulated annealing scheme while maintaining high degree of diversity. The proposed optimization scheme is implemented using Ocean script in Cadence Virtuoso environment without any loss of generality. Design optimization of a 2.4GHz low noise amplifier (LNA) for the minimum noise figure (NF) subjected to design constraints, i.e. power consumption, feature size etc. is performed and effectiveness of l-HPSO is verified by comparing the results with state-of-art optimization techniques. © 2016 IEEE.